Mathematical Communication Skills Viewed from Self Regulated Learning (SRL) using LAPS-Heuristic Model with Guilford Approach (Universitas Negeri Semarang, 2019)
This study has the purpose of determining the quality of the learning using LAPS-Heuristic model with Guilford approach in achieving the students' mathematical communication skill and their skills patterns viewed from self-regulated learning (SRL). The research method used was a mixed method with an explanatory sequential design. The first stage was quantitative data collection, and it was done using questionnaires to categorized the subject and tests. The next stage was qualitative data collection, and it was done using triangulation techniques such as questionnaires, tests, and interviews. Based on the analysis and discussion, it can be concluded that: the learning with the LAPS-Heuristic model with Guilford approach is categorized in a very good quality in achieving the mathematical communication, seen from the classical completeness of the experimental class which is more than 75%, the classical completeness is better, the average of mathematical communication skill is better, the n-gain increased in the medium category, the mathematical communication skills in subjects with high SRL tend to meet the aspects of writing information, making mathematical models, and drawing diagrams very well; subjects with moderate SRL tend to fulfill aspects of writing information, making mathematical models, and drawing diagrams quite well; subjects with low SRL tend to have lack aspects of writing information, making mathematical models and drawing diagrams.